The ethics of aggregation in cost-effectiveness analysis or, “on books, bookshelves, and budget impact” - Charlton, Victoria (Frontiers in Health Services, 2022)
In deciding how to allocate resources, healthcare priority-setters are increasingly paying attention to an intervention's budget impact alongside its cost-effectiveness. Some argue that approaches that use budget impact as a substantive consideration unfairly disadvantage individuals who belong to large patient groups. Others reject such claims of “numerical discrimination” on the grounds that consideration of the full budget impact of an intervention's adoption is necessary to properly estimate opportunity cost. This paper summarizes this debate and advances a new argument against modifying the cost-effectiveness threshold used for decision-making based on a technology's anticipated budget impact. In making this argument, the paper sets out how the apparent link between budget impact and opportunity cost is largely broken if the effects of a technology's adoption are disaggregated, while highlighting that the theoretical aggregation of effects during cost-effectiveness analysis likely only poorly reflects the operation of the health system in practice. As such, it identifies a need for healthcare priority-setters to be cognizant of the ethical implications associated with aggregating the effects of a technology's adoption for the purpose of decision-making. Throughout the paper, these arguments are illustrated with reference to a “bookshelf” analogy borrowed from previous work.